UPAYA DIPLOMASI KOREA SELATAN MEMPERBAIKI HUBUNGAN EKONOMI DENGAN TIONGKOK PASCA PEMASALAHAN TERMINAL HIGH ALTITUDE AREA DEFENSE (THAAD) - Paramitha, Made Cynthia; Parameswari, A.A. Ayu Intan; Widya Nugraha, A.A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2021): Jurnal DIKSHI, 2021)
This study aims to describe South Korea's efforts to improve economic relations with Tiongkok after the economic sanctions imposed by Tiongkok on South Korea due to South Korea's decision to install a Terminal High Altitude Area Defense (THAAD) in South Korea. This research uses qualitative methods with literature study and secondary data. This study uses the concepts of foreign policy and diplomacy to see South Korea's diplomatic efforts to improve economic relations with Tiongkok. The results of this study indicate that South Korea's diplomatic efforts to improve economic relations with Tiongkok are based on South Korea's economic interests towards Tiongkok, which is South Korea's largest trading partner which controls a quarter of South Korea's total export volume. The conclusion of this research is that South Korea's diplomatic efforts to improve relations with Tiongkok were carried out by communicating and negotiating in various meetings with Tiongkok. Keywords: South Korea, Tiongkok, Diplomacy, THAAD.